Stochastic resonance in an RF SQUID with shunted ScS junction - Turutanov, O.; Golovanevskiy, Vladimir; Lyakhno, V.; Shnyrkov, V. (Elsevier BV * North-Holland, 2013)
Using a point (superconductor–constriction–superconductor, ScS) contact in a single-Josephson-junction superconducting quantum interference device (RF SQUID) provides stochastic resonance conditions at any arbitrary small value of loop inductance and contact critical current, unlike SQUIDs with more traditional tunnel (superconductor–insulator–superconductor, SIS) junctions. This is due to the unusual potential energy of the ScS RF SQUID which always has a barrier between two wells, thus making the device bistable. This paper presents the results of a numerical simulation of the stochastic dynamics of the magnetic flux in an ScS RF SQUID loop affected by band-limited white Gaussian noise and low-frequency sine signals of small and moderate amplitudes. The difference in stochastic amplification of RF SQUID loops incorporating ScS and SIS junctions is discussed.